Development of a near infrared protein nanoprobe targeting Thomsen-Friedenreich antigen for intraoperative detection of submillimeter nodules in an ovarian peritoneal carcinomatosis mouse model. (May 2020) - Coustets, Mathilde; Ladurantie, Caroline; Bellard, Elisabeth; Prat, Mélissa; Rols, Marie-Pierre; Ecochard, Vincent; Ferron, Gwenaël; Chabot, Sophie; Golzio, Muriel; Paquereau, Laurent
Abstract: The epithelial ovarian cancer is one of the most lethal gynecological malignancy due to its late diagnostic and many relapses observed after first line of treatment. Once diagnose, the most important prognostic factor is the completeness of cytoreductive surgery. To achieve this goal, surgeons have to pinpoint and remove nodules, especially the smallest nodules. Recent advances in fluorescence-guided surgery led us to develop a recombinant lectin as a nanoprobe for the microscopic detection of nodules in the peritoneal cavity of tumor-bearing mice. This lectin has an intrinsic specificity for a carcinoma-associated glycan biomarker, the Thomsen-Friedenreich antigen. In this study, after its labelling by a near infrared dye, we first demonstrated that this nanoprobe allowed indirect detection of nodules already implanted in the peritoneal cavity, through tumor microenvironment targeting. Secondly, in a protocol mimicking the scattering of cells during surgery, we obtained a direct and long-lasting detection of tumor cells in vivo . This lectin as already been described as a nanocontainer able to do targeted delivery of a therapeutic compound to carcinoma cells. Future developments will focus on the combination of the nanoprobe and nanocontainer aspects in an intraperitoneal nanotheranostic approach. Graphical abstract: Image 1